Enhanced formation and impaired degradation of neutrophil extracellular traps in dermatomyositis and polymyositis: a potential contributor to interstitial lung disease complications. (9th June 2014) - Zhang, S; Shu, X; Tian, X; Chen, F; Lu, X; Wang, G
Summary: Dermatomyositis (DM) and polymyosits (PM) are systemic autoimmune diseases whose pathogeneses remain unclear. Neutrophil extracellular traps (NETs) are reputed to play an important role in the pathogenesis of autoimmune diseases. This study tests the hypothesis that NETs may be pathogenic in DM/PM. Plasma samples from 97 DM/PM patients (72 DM, 25 PM) and 54 healthy controls were tested for the capacities to induce and degrade NETs. Plasma DNase I activity was tested to further explore possible reasons for the incomplete degradation of NETs. Results from 35 DM patients and seven PM patients with interstitial lung disease (ILD) were compared with results from DM/PM patients without ILD. Compared with control subjects, DM/PM patients exhibited a significantly enhanced capacity for inducing NETs, which was supported by elevated levels of plasma LL-37 and circulating cell-free DNA (cfDNA) in DM/PM. NETs degradation and DNase I activity were also decreased significantly in DM/PM patients and were correlated positively. Moreover, DM/PM patients with ILD exhibited the lowest NETs degradation in vitro due to the decrease in DNase I activity. DNase I activity in patients with anti-Jo-1 antibodies was significantly lower than in patients without. Glucocorticoid therapy seems to improve DNase I activity. Our findings demonstrate that excessively formed NETs cannot be degraded completely because of decreased DNase I activity in DM/PM patients, especially in patients with ILD, suggesting that abnormal regulation of NETs may be involved in the pathogenesis of DM/PM and could be one of the factors that initiate and aggravate ILD.